Conception and policy implications of photovoltaic modules end‐of‐life management in China. Issue 1 (17th July 2020) - Li, Yan; Wang, Ge; Shen, Bo; Zhang, Qi; Liu, Boyu; Xu, Ruoxi
Abstract: China has become the world's largest market for photovoltaic (PV). Effective management of end‐of‐life PV components is critical to the sustainable development of renewable energy. However, the scale of PV recycle industry is still small in China, and there is a lack of supporting policies and public attention. Issues and solutions regarding PV end‐of‐life management have not been well covered by the research community, and this article aimed at filling this gap. This article first examined the growing need for PV modules end‐of‐life management in China as a result of rapid PV installation expansion fueled by governments' policy promotion and fiscal incentives, especially with special programs such as the Photovoltaic Poverty Alleviation Initiative. Then, factors leading to the PV components recycling issues, policies adopted in other countries and regions to promote PV recycle, and various business modes that can be applied to enable PV recycle were reviewed. Finally, a more effective institutional hierarchy was presented for PV modules end‐of‐life management, with a set of specific recommendations on actions that can help strengthen PV end‐of‐life management. This article is categorized under: Photovoltaics > Economics and Policy Photovoltaics > Systems and Infrastructure Abstract : Hierarchy for PV system components end‐of‐life management in China.